Mystery on the Lego Express - King, Trey; Wang, Sean, 1970- (New York, NY : Scholastic Inc., 2014)
Mr. Clue's vacation gets put on hold when a famous actress asks for his help on the express train to find a thief.
Ages 3-6.
AD 530
Accelerated Reader AR
Keywords: LEGO toys -- Juvenile fiction; Railroad trains -- Juvenile fiction; Detective and mystery stories